Pengaruh Media Video Animasi Terhadap Motivasi Belajar Pendidikan Agama Kristen & Budi Pekerti Siswa Kelas XII SMA Negeri 1 Uluan Kabupaten Toba Tahun Pembelajaran 2022/2023 - Sinta Sinaga; Tianggur Medi Napitupulu; Limmarten Simatupang; Tiurma Barasa; Franskoy Rio Naibaho (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The aim of this research is to determine the positive and significant influence of animated video media on learning motivation for Christian religious education and character in class The research method used in this research is a quantitative method with a descriptive statistical approach. The population is the entire class of class Data was collected using a positive closed questionnaire with 36 items. The results of data analysis show that there is a positive and significant influence between animated video media and the learning motivation of students at XII SMA Negeri 1 Uluan for the 2022/2023 academic year: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.397> rtable( α = 0.05, IK = 95%, n = 43) = 0.301, thus it is known that there is a positive relationship between variable dk=n-2=41)=2.021, thus there is a significant relationship between variable b) Regression coefficient of determination test (r²)=15.8%. 3) Test the hypothesis using the F test to obtain Fcount>Ftable, namely 7.67>1.92. Thus Ha is accepted and H0 is rejected. Thus, it can be seen that the research hypothesis proposed by the author is accepted, namely that there is a positive and significant influence between animated video media and the learning motivation of students at XII SMA Negeri 1 Uluan for the 2022/2023 academic year.